Wild edible plants collected and consumed by the locals in Daqinggou, Inner Mongolia, China - Sachula; Geilebagan; Yan-ying Zhang; Hui Zhao; Khasbagan (BMC, 2020)
Abstract Background Knowledge of wild edible plants is an important part of traditional knowledge. It is closely related to traditional human agriculture, as well as biodiversity. This study aimed to conduct a detailed investigation and evaluation of wild edible plants that are collected and consumed by the Mongolian and Han locals in Daqinggou and to provide valuable data for the development and utilization of plant resources. Methods In the 9 site visits to the area of Daqinggou during the period of 2017-2019, the authors used key informant interviews, semistructured interviews, and questionnaires to collect utilization information regarding precollected species of local wild edible plants. By combining the data obtained from 101 key informants, the authors used the Cultural Food Significance Index (CFSI), a quantitative index to evaluate the relative importance of the wild edible plants that were discussed in the aforementioned interviews. Results The investigation results show that the Mongolian people provided 67 folk names, corresponding to 57 wild plants, and the Han Chinese provided 58 folk names, corresponding to 49 wild plants. A total of 61 edible wild plant species belonging to 29 families and 52 genera were recorded as edible resources for the locals in Daqinggou. The uses include grains, oil and fat resources, vegetables, fruits, beverages, condiments, and snacks. The most commonly reported purpose of wild edible plants is using them as vegetables, followed by using them as beverages and fruits. The most widely used edible parts are fruits, leaves, and other aerial parts. Eating raw and cooked plants are the usual methods of consuming wild edible plants according to the locals. In addition, the CFSI of 61 wild edible plant species shows that 27 species have characteristics of medical food. Conclusions The knowledge and experience of naming and consuming wild plants by the Mongolian people and Han Chinese in Daqinggou are an important manifestation of the direct interaction between locals and plants. The CSFI evaluation of the wild edible plants consumed by the locals in Daqinggou establishes the utilization of some wild plants as part of the traditional knowledge of medical food.